2018
DOI: 10.31616/asj.2018.12.4.710
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Microscope-Assisted Stand-Alone Transarticular Screw Fixation without Gallie Supplementation in the Management of Mobile Atlantoaxial Instability

Abstract: Study Design Retrospective study.PurposeTo evaluate the clinico-radiological efficacy of stand-alone minimally invasive transarticular screw (MIS-TAS) fixation without supplemental Gallie fixation in the management of mobile C1–C2 instability.Overview of LiteratureData evaluating the efficacy and feasibility of MIS-TAS in the literature is scanty.MethodsPatients with mobile atlantoaxial instability and >2 years follow-up were included and managed by stand-alone TAS fixation using the Magerl technique and morse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…For a patient population as mentioned above, IPTSFC1/C2 may represent a safe surgical treatment option with the smallest possible surgical trauma to enable rapid remobilization and dehospitalization. Our data agree with those found in the literature on this subject 12 14 . The advantage of percutaneous transarticular screw fixation over the classic transarticular screw fixation of C1 and C2 as an open approach is the significantly lower surgical invasiveness 10 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For a patient population as mentioned above, IPTSFC1/C2 may represent a safe surgical treatment option with the smallest possible surgical trauma to enable rapid remobilization and dehospitalization. Our data agree with those found in the literature on this subject 12 14 . The advantage of percutaneous transarticular screw fixation over the classic transarticular screw fixation of C1 and C2 as an open approach is the significantly lower surgical invasiveness 10 .…”
Section: Discussionsupporting
confidence: 93%
“…The IPTSFC1/C2 as another minimally invasive therapy option available, seems to be quite worthwhile. Furthermore, it has been shown that minimally invasive percutaneous transarticular screw fixation of C1/C2 combined with a mini open technique to establish spinal fusion resulted in fusion rates of 97.5 to 98% 12 , 13 . These rates were similar to spinal fusion rates achieved with classic transarticular screw fixation with dorsal bone grafting between C1 and C2 3 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason we arrived at this hypothesis was because of multiple literature reporting that a sustained excellent outcome is possible despite wire failure. In our previous study we found a fusion rate of 97.5% without the use of wires 10) . Matsumoto et al and Ito et al in their articles mentioned a fusion rate of 95% and 100% respectively despite their cases having confirmation of wire loosening 4,6) .…”
Section: Discussionmentioning
confidence: 82%